2020
DOI: 10.1108/jd-04-2019-0074
|View full text |Cite
|
Sign up to set email alerts
|

“People are reading your work,” scholarly identity and social networking sites

Abstract: PurposeScholarly identity refers to endeavors by scholars to promote their reputation, work and networks using online platforms such as ResearchGate, Academia.edu and Twitter. This exploratory research investigates benefits and drawbacks of scholarly identity efforts and avenues for potential library support.Design/methodology/approachDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Radford, V. Kitzie, S. Mikitish, D. Floegel, G.P Radford, L.S. Connaway (Radford et al, 2020). The authors conducted qualitative research considering the impact on scientific identity of online platforms such as ResearchGate, Academia.edu, and Twitter.…”
Section: Impression Management In the Context Of Social Interaction (...mentioning
confidence: 99%
See 1 more Smart Citation
“…Radford, V. Kitzie, S. Mikitish, D. Floegel, G.P Radford, L.S. Connaway (Radford et al, 2020). The authors conducted qualitative research considering the impact on scientific identity of online platforms such as ResearchGate, Academia.edu, and Twitter.…”
Section: Impression Management In the Context Of Social Interaction (...mentioning
confidence: 99%
“…The authors use "scholarly identity platforms" in their areas of interest, concluding that they benefit from development opportunities or support academic libraries. On the other hand, they indicated that their participation is also associated with reputational risk (Radford et al, 2020). The public discourse of scientists is related to their identity.…”
Section: Impression Management In the Context Of Social Interaction (...mentioning
confidence: 99%
“…Although several studies have found that non-use or very limited use of web profiles is common (e.g. Bukvova, 2012;Francke, 2019;Greifeneder et al, 2018;Van Noorden, 2014), other studies with researchers (primarily but not exclusively from the Global North) have shown what features encourage use of profiles both as author and as audience (Greifeneder et al, 2018;Jordan, 2019a;Jordan and Weller, 2018;Kjellberg and Haider, 2018;Meishar-Tal and Pieterse, 2017;Nicholas et al, 2014;Radford et al, 2020;Van Noorden, 2014). These features range from networking opportunities to keeping up-to-date and to promoting one's work.…”
Section: Platform Affordancesmentioning
confidence: 99%
“…Concern with the credibility of the for-profit platforms hosting the profiles has also been voiced in interviews with researchers (e.g. Radford et al , 2020). In their estimation of what factors may contribute to building reputation for a researcher, based on a literature review, Herman and Nicholas (2019) conclude that several academic activities may be of importance for reputation but that teaching has the least potential.…”
Section: Presenting the Public Researcher “Self”mentioning
confidence: 99%
See 1 more Smart Citation